Effective fraction of Teucrium polium suppressed polyol pathway through inhibiting the aldose reductase enzyme: strategy to reduce retinopathy - Somayeh Amraee; Seifollah Bahramikia; Abdelnasser Mohammadi (Institue of Medicinal Plants, ACECR, 2020)
Background: Several metabolic pathways are involved in the complications of diabetes like polyol pathway. Aldose reductase (AR) is a key enzyme in the polyol pathway, which catalyzes the conversion of glucose to sorbitol. AR inhibitors are appropriate to prevent and treat the diabetes complications. Objective: This study was designed to investigate the effect of different fractions of Teucrium polium on the AR activity. Methods: Fifty cow's eye lenses were prepared and AR enzyme was purified according to the Hyman-Kinoshita method. The enzyme activity in the presence of the crude extract and different fractions of Teucrium polium (1, 5, 10, 20 and 100 μg/ml) was measured. In addition, IC50 content of fractions was also measured for the neutralization of DPPH free radical. Since some AR inhibitors are phenolic compounds, the phenolic and flavonoid contents have been investigated. Results: Results showed that the highest phenol and flavonoid content and the lowest IC50 value (3.67 µg/ml) for AR inhibition were related to the ethyl acetate fraction. Line weaver-Burk plot showed that ethyl acetate fraction acts as a non-competitive enzyme inhibition. Conclusion: Thus, T. polium can be proposed as a therapy to prevent or treat chronic complications of diabetes in the future.